Comparison of Clinical Efficacy and Safety Between da Vinci Robotic and Laparoscopic Intersphincteric Resection for Low Rectal Cancer: A Meta-Analysis - Jie Zhang (Frontiers Media S.A., 2021)
Background and Aims: The intersphincteric resection (ISR) is beneficial for saving patients' anus to a large extent and restoring original bowel continuity. Laparoscopic ISR (L-ISR) has its drawbacks, such as two-dimensional images, low motion flexibility, and unstable lens. Recently, da Vinci robotic ISR (R-ISR) is increasingly used worldwide. The purpose of this article is to compare the feasibility, safety, oncological outcomes, and clinical efficacy of R-ISR vs. L-ISR for low rectal cancer.Methods: PubMed, EMBASE, Cochrane Library, and Web of Science were searched to identify comparative studies of R-ISR vs. L-ISR. Demographic, clinical, and outcome data were extracted. Mean difference (MD) and risk ratio (RR) with their corresponding confidence intervals (CIs) were calculated.Results: Five studies were included. In total, 510 patients were included, of whom 273 underwent R-ISR and 237 L-ISR. Compared with L-ISR, R-ISR has significantly lower estimated intraoperative blood loss (MD = −23.31, 95% CI [−41.98, −4.64], P = 0.01), longer operative time (MD = 51.77, 95% CI [25.68, 77.86], P = 0.0001), hospitalization days (MD = −1.52, 95% CI [−2.10, 0.94], P < 0.00001), and postoperative urinary complications (RR = 0.36, 95% CI [0.16, 0.82], P = 0.02).Conclusions: The potential benefits of R-ISR are considered as a safe and feasible alternative choice for the treatment of low rectal tumors.